FORMING PURCHASE INTENTIONS ON PLANT-BASED FOOD PRODUCTS DURING COVID-19 PANDEMIC - Angwyn, Angeline; Soelasih, Yasintha; Ho, Shu-Hsun (jfpublisher, 2022)
This research intends to test and analyze the influence of influences factors such as health consciousness, environmental concern, social influence, and perceived attributes on plant-based food products purchase intention. The aim of this research also wants to know the impact of covid-19, which acts as a moderator, and consumer attitudes as a mediator of the influences factors tested on purchase intention. Our research was conducted on 338 respondents using google form as the distribution medium, of which 283 respondents were Indonesian, and 55 respondents were Taiwanese respondents. Data processing in this research used the partial least squares structural equation model (PLS-SEM) with SmartPLS 3 software. The result shows the direct influence of influence factors, namely health consciousness, social influence, and perceived attributes to plant-based food product purchase intentions. In addition, indicators that act as mediators and mediation on social influence and perceived attributes factors, namely covid-19 impact and attitude, also give positive results to plant-based food products purchase intention. However, this research also found no direct effect of influences factors environmental concern on plant-based food products purchase intention.